Neuropathic pain and deep brain stimulation. - Pereira, E; Aziz, T (2014)
Deep brain stimulation (DBS) is a neurosurgical intervention the efficacy, safety, and utility of which are established in the treatment of Parkinson's disease. For the treatment of chronic, neuropathic pain refractory to medical therapies, many prospective case series have been reported, but few have published findings from patients treated with current standards of neuroimaging and stimulator technology over the last decade . We summarize the history, science, selection, assessment, surgery, programming, and personal clinical experience of DBS of the ventral posterior thalamus, periventricular/periaqueductal gray matter, and latterly rostral anterior cingulate cortex (Cg24) in 113 patients treated at 2 centers (John Radcliffe, Oxford, UK, and Hospital de São João, Porto, Portugal) over 13 years. Several experienced centers continue DBS for chronic pain, with success in selected patients, in particular those with pain after amputation, brachial plexus injury, stroke, and cephalalgias including anesthesia dolorosa. Other successes include pain after multiple sclerosis and spine injury. Somatotopic coverage during awake surgery is important in our technique, with cingulate DBS under general anesthesia considered for whole or hemibody pain, or after unsuccessful DBS of other targets. Findings discussed from neuroimaging modalities, invasive neurophysiological insights from local field potential recording, and autonomic assessments may translate into improved patient selection and enhanced efficacy, encouraging larger clinical trials.